Purchase of Scanning Electron Microscope [Tender documents : T21557792] (MENA Report, 2014)
Procurement subject is common procurement of capital equipment for the center for micro and nano science and technology, university of rijeka: scanning (scanning) electron microscope (sem), cpv 38511100-1. the system should be offered as a whole, including all the equipment and supplies needed for its installation and verification system. procurement subject includes delivery, introduction to the use of equipment, assembly, installation,...